Soccer players and coaches` perspectives towards ergogenic aids and supplement use in the Ethekwini region - Kisten, T.; Naidoo, R. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Doping is regarded as a form of cheating where athletes use substances that are on the prohibited list, predominantly for gaining an edge over their competitors. Where sports participation was previously seen as recreational activity, it is now an intense environment for the adolescent athlete, placing high demands for performance in order to get drafted into professional sports. There is increased pressure on athletes to perform. This leads to increase use of performance enhancing substances and supplements to achieve increased performance levels and cope with the heavy demands that are placed on the player. Aim: The aim of this study was to determine the perspectives of U-19 soccer players and their coaches towards the use of ergogenic aids and supplements in the eThekwini region, KwaZulu-Natal. Methodology: The study was a mixed-methods design. Both quantitative and qualitative designs were employed. The sample comprised of participants playing first team U-19 soccer from clubs in the eThekwini region and their respective coaches. A questionnaire was administered to players to assess the knowledge, attitudes and practices towards doping in sport, to determine their source of information and to determine which supplement was most frequently used. An interview was conducted with the coaches to assess his/her knowledge, attitude and beliefs about supplementation, and where do they get their information from about supplements. Both descriptive and inferential statistics were employed to analyse and report the data. Results: The U-19 soccer players and coaches believed that consuming prohibited substances in sport is unethical. Majority of the U-19 soccer players (73.9% either agreed or strongly agree) and coaches believed that doping in soccer is on the increase. Almost a quarter (24.7%) of the U-19 soccer players consumed performance enhancing substances (PES), cannabis, alcohol and/or smoke. Coaches believed that there players do not consume PES or substances. Majority (84.4%) of the U-19 soccer players and majority of coaches stated that educational programmes are needed. Conclusion: The U-19 soccer players and coaches believe that doping is prevalent in soccer. Players and coaches believe that sport organisations need to implement more educational programmes about doping and on how to consume PES.